1980
DOI: 10.1099/00221287-117-1-235
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Cellulase Production by Sporocytophaga myxococcoides NCIB 8639

Abstract: Sporocytophaga myxococcoides NCIB 8639 utilized a number of cellulosic substrates and produced extracellular carboxymethylcellulase and activity towards Avicel (a milled microcrystalline cellulose powder). Both types of enzyme were synthesized in media containing glucose but the activity was influenced by the nature and concentration of the carbon source. The ratio of carboxymethylcellulase activities measured by reducing sugar production and by viscosity decrease was also influenced by the nature of the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The components of the culture media exert variable effects on the quality and quantity of particular pectic enzymes. The secretion of cellulase enzyme by plant pathogenic fungi depends on the type of culture media used (VANCE et al 1980;MEHTA and MEHTA 1985). Maximum protease enzyme production by all the three isolates was found in BROWN'S and peptone dextrose media.…”
Section: Resultsmentioning
confidence: 97%
“…The components of the culture media exert variable effects on the quality and quantity of particular pectic enzymes. The secretion of cellulase enzyme by plant pathogenic fungi depends on the type of culture media used (VANCE et al 1980;MEHTA and MEHTA 1985). Maximum protease enzyme production by all the three isolates was found in BROWN'S and peptone dextrose media.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the sub-o?timal operating conditions, which included a superficial air velocity of 5.1cms -±, the dissolved oxygen concentration did not fall below 75% saturation. Figure 3 shows that the growth of ~ myxococcoides in the ALF followed a similar pattern to that described for a stirred-tank fermenter (STF) (Vance et al, 1980) with extracellular carboxymethylcellulase production occurring during the log phase. The maximum enzyme activity, however, was some 150 units ml -I lower than in the STF.…”
mentioning
confidence: 74%
“…The kLa of the fermenter was determined under various conditions by the dynamic method of Bandyopadhyay and Humphrey (1967) using the oxygen electrode previously described (Vance et al, 1980). Figure 2 shows that the kLa of the fermenter could be increased by using a less porous sinter and by increasing the superficial air velocity up to a critical value of approximately 7 cm s-L above which bubble coalescence appeared to take place.…”
Section: Methodsmentioning
confidence: 99%
“…(1972a), it was demonstrated that strain LX-7 forms an extracellular exocellulase which degrades crystalline cellulose such as Avicel, cellulose powder MN300, cc-cellulose and is detectable when assayed by measuring the soluble carbohydrate released, but no significant activity was detected by assaying the reducing sugars production. Although Berg et al (1972a) did not provide experimental detail, it is possible that assaying for soluble sugars production may he a more sensitive way of detecting exocellulase than assaying for reducing sugars, par- (Berg et al 1972b) and Sporocytophagu myxococcoides which was found 60% decomposition of Avicel over 4 d incubation (Vance et al 1980); strain LX-7 digested cellulose completely in 4 6 d.…”
Section: Discussionmentioning
confidence: 99%